Composição do leite e diagnóstico de mastite em caprinos - Correa, Carina Morais; Michaelsen, Raquel; Ribeiro, Maria Edi da Rocha; Pinto, Andrea Troller; Zanela, Maira Balbinotti; Schmidt, Verônica (Acta Scientiae Veterinariae, 2018)
Background: Milk is one of the most used foodstuffs by humans in their diet. The quality of goat milk is already regulated by Law, which takes into consideration its physical-chemical and microbiological composition parameters. Several factors contribute for the alteration of the physical-chemical and microbiological parameters of caprine milk. These include breed, age, lactation phase and diet, among others. The health status of animals may interfere in the quality of the milk produced, both regarding food safety and milk processing and, for that reason, the identification of mastitis-causing agents is important, so that prevention and control measures can be implemented. The present study aimed at analyzing the occurrence of mastitis and the milk composition of dairy goats in a semi-intensive production system. Materials, Methods & Results: In a private goat farm with a flock composed of 32 female animals of breeds such as Saanen and Anglo-Nubian, raised on a semi-confined system, the diagnosis of mastitis was made through methods such as California Mastitis Test (CMT), Somatic Cells Count (SCC) and bacterial isolation. A total of 136 milk samples were analyzed, which were individualized per teat. Additionally, the study determined the volume of milk produced individually and the chemical composition of milk samples (fat, raw protein, lactose and total solids). In 37 (27.2%) samples, subclinical mastitis caused by CNS was identified. A negative response to CMT was observed in 125 (91.92%) samples. Only four samples presented a coincidence (OR=1.239) between CMT and bacterial isolation (P=0.7470). It was observed that the daily milk production ranged between 207.90 mL and 2.68 L. Moreover, it became clear that the milk production in half of the teats with subclinical mastitis was smaller (P=0.0026). A tendency to a significant reduction (p< 0.001) in the percentage of fat and total solids was verified. The lactose percentage remained stable during the four months, and that of protein showed a tendency to reduction (p<0.001). A great variability in SCC was observed (23,000 to 9,999,000 cel.mL-1) during the sampling months. A significant concordance (P<0.001) was determined between a low SCC and the non-bacterial isolation in 65 samples (OR=11.556). Discussion: Mastitis is an inflammation of the mammary gland and, in the majority of cases, it is manifested in its subclinical form, having CNS as its main agent, both in Brazil and in other countries. Methods such as bacterial isolation, SCC and CMT are used for the diagnosis of mastitis. In the present study, no relation among these diagnostic methods has been found. This fact had already been reported in Brazilian literature. The herd configuration may have contributed for the occurrence of mastitis, since this disease is influenced by genetic factors and age. Moreover, its occurrence was higher in Anglo-Nubian females which, in addition to being older and consequently having undergone a higher number of lactations, presented an udder conformation with fragile ligaments and pending teats. Such conformation of the mammary glands may collaborate to the occurrence of infection. Mastitis is responsible for damages in the dairy production system, due to economical losses and reduction in the quality and volume of milk. However, the present study did not observe a variation in milk production due to bacterial contamination or an increase of SCC. A reduction in solid and fat contents did coincide with the beginning of the lactation period in Saanen goats; animals belonging to this breed tend to produce a higher volume of milk and, consequently, a smaller proportion of its components is observed. Based on the results obtained, the study concluded that the herd composition with regard to breed and lactation phase has an influence in the occurrence of subclinical mastitis, as well as in milk composition. Methods such as the CMT and SCC should be used carefully in the diagnosis of mastitis in goats.